1935
DOI: 10.1017/s0022172400032459
|View full text |Cite
|
Sign up to set email alerts
|

Virulence and Immunogenic Activities ofB. Typhosusin Relation to its Antigenic Constituents

Abstract: 1. Rough variants, derived from strains of B. typhosus which possess the Vi antigen, may still contain this antigen though the smooth O antigen has been lost.2. Such variants, which are non-virulent, are yet capable of inducing active and passive immunity.3. The virulence of B. typhosus depends on the combined activity of the smooth O and the Vi antigen. Nevertheless the Vi antibody alone is sufficient to protect against infection with strains of the highly virulent type.4. The use of avirulent, rough, but Vi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

1936
1936
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…The possession of T antigen by these strains was also readily demonstrated by immunization of rabbits and by absorption experiments. A similar blocking of the agglutination reactions due to one antigen by the presence of another has been observed with other bacteria, for example, with the Vi antigen of the typhoid bacillus (3)(4)(5). Blocking of M agglutination reactions in type 1 has been previously reported (1).…”
Section: Discussionsupporting
confidence: 64%
“…The possession of T antigen by these strains was also readily demonstrated by immunization of rabbits and by absorption experiments. A similar blocking of the agglutination reactions due to one antigen by the presence of another has been observed with other bacteria, for example, with the Vi antigen of the typhoid bacillus (3)(4)(5). Blocking of M agglutination reactions in type 1 has been previously reported (1).…”
Section: Discussionsupporting
confidence: 64%
“…E. faecalis, Bacillus cereus, Staphylococcus aureus). Finally, similar attenuation of E. coli K12 and E. coli ECOR 10 suggests that fecal pathogens, which are typically smooth strains (Felix and Pitt, 1935), would be as effectively removed as our model indicator E. coli K12. Overall, these results are promising for the application of Fe-EC to drinking water or wastewater treatment.…”
Section: Attenuation Of Different Types Of Bacteriamentioning
confidence: 80%
“…This investigation included a study of seven strains of varied virulence and it was found that, as measured by active-immunity mouse-protection tests and by "0" agglutinin and mouse-protective antibody responses in human volunteers, vaccines prepared from virulent strains were more highly immunogenic than were those prepared from avirulent strains. Felix (7) likewise reported that highly virulent strains of S. typhosa exhibited the greatest immunizing activity. He placed major emphasis on the r61e played by Vi antigen both in virulence and in immunogenicity.…”
mentioning
confidence: 99%